Do capital requirements affect bank efficiency? Evidence from China - Pierre Pessarossi; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper contributes to the debate on the effect of capital requirements on bank effieciency. We study the relation between capital ratio and bank efficiency for Chinese banks over the period 2004?2009, taking advantage of the profound regulatory changes in capital requirements that occurred during this period to measure the exogenous impact of an in-crease in the capital ratio on banks' cost efficiency. We find that such an increase has a positive effect on cost efficiency, the size of which depends to an extent on the bank's ownership type. Our results therefore suggest that capital requirements can improve bank efficiency.
URN:NBN:fi:bof-201408071977
Keywords: G21; G28; 330; bank; capital requirements; efficiency; China